Dynamics of aerial and perennial biomass of two lucerne cultivars with different fall dormancy subject to two severities of cutting during the establishment phase - García, Leonela Analía (2021)
The aim of this study was to quantify the impact of two cutting severities on the dynamics of aerial and perennial (root plus crown) biomass of lucerne (Medicago sativa L.) plants of two cultivars of contrasting fall dormancy rating during the establishment phase. We worked at Unidad Integrada Balcarce with two cultivars of lucerne (non-winter dormant: FD10; semi-winter dormant: FD6) and two cutting severities (40 and 100 mm) defining four treatments (FD6-40 mm, FD6-100 mm, FD10-40 mm and FD10-100 mm) under a completely randomized design. In both cultivars, increasing cutting severity produced a reduction in leaf area and number of nodes in the residual, resulting in a reduced production of aerial biomass during regrowth, given a reduction on shoot number. On the other hand, the effect of increased cutting severity on perennial biomass was only observed in plants of FD10 cultivar. This cultivar showed less perennial biomass when cut at 40 mm than at 100 mm, while no differences were observed between cutting heights in FD6 cultivar.